Comparative Analysis of the Formation and Development of Ethnic Press in Gagauzia and Tuva (20th–21st Centuries) - Mammadov, Sabir R. (The New Research of Tuva, 2025)
The article presents a comparative analysis of the ethnic press of the Gagauz and Tuvan peoples — two kindred Turkic groups historically residing in geographically distant territories, namely Southern Bessarabia and Southern Siberia. Despite distinct geopolitical conditions, both communities have undergone parallel paths of development. Ethnic publications are understood as newspapers, journals, almanacs, and bulletins published in the language of the respective ethnic group; they address issues of civic life and culture, disseminate ethnic values, facilitate self-awareness of the community, promote its consolidation, and mobilize readers for the resolution of immediate tasks.The author examines the historical evolution of Gagauz and Tuvan ethnic press from its inception in the 1920–1930s, through the periods of the “thaw”, “perestroika”, and the stage of democratization of public life. The history of the press is analyzed against a broad social backdrop and in the context of political events across the century. Parallels are drawn between the processes in Gagauzia and Tuva, similarities are revealed, and distinctive features are highlighted.It is shown that ethnic publications not only comprehensively reflect the life of their people but also serve as principal initiators and creators of diverse forms and methods for strengthening ethnic identity. The study points out that ethnic periodicals, which unite national elites and a vast readership, also act as centers of statehood and public governance.Comparative analysis allows the assertion that, due to the relatively larger population of Tuvans compared to the Gagauz, the formation of a stable ethnic elite, the availability of scholars in various research fields, and other resources characteristic of a titular ethnicity, the structure and reach of the Tuvan ethnic press are more advanced, conferring certain advantages.
Keywords: Gagauz; Tuvan; native language; Tuvan language; mass media; ethnic press; ethnic publications; tradition; ethnic culture; Turkic world